Advances in Lodging Resistance of Rice Since the"Green Revolution" - Xiaofei WANG; Zhanhua LU; Wei LIU; Dongbai LU; Shiguang WANG; Haoxiang WU; Zhiqiang FANG; Xiuying HE (Guangdong nongye kexue, 2022)
Rice is one of the food crops with the largest planting area and the highest total output in China, which plays an important role in ensuring national food security. Since the "Green Revolution", China's rice yield per unit area has been greatly improved. However, the lodging problem of rice has long restricted the high and stable yield and excellent quality of rice. A large area of lodging of rice will lead to serious yield loss and rice quality decline. At present, with the continuous improvement of rice yield per unit area, the problem of rice lodging is becoming increasingly prominent, which has been one of the great hidden dangers threatening the normal rice production. Through decades of continuous research, researchers at home and abroad have made great progress in the cause, mechanism, influencing factors, evaluation methods and lodging resistance genetics and breeding of rice. The study summarizes the research progress of rice lodging resistance since the"Green Revolution", combined with the lodging resistance research work experience for many years, comprehensive analyzes the research the origin of rice lodging resistance, clarifies the properties of rice lodging, summarizes the main related factors of rice lodging resistance, and puts forward the relevant countermeasures to raise the capacity of rice lodging resistance. On the basis of the existing research, the main directions of rice lodging resistance breeding, cultivation and molecular mechanism research in the new era are prospected in order to provide references for rice lodging resistance researchers.